Acne fulminans associated with lymecycline intake: a case report - Gualtieri B; Tonini A; Panduri S; Chiricozzi A; Romanelli M (Dove Medical Press, 2018)
Bruno Gualtieri, Annalisa Tonini, Salvatore Panduri, Andrea Chiricozzi, Marco Romanelli Department of Dermatology, University of Pisa, Pisa, Italy Abstract: Acne fulminans (AF) is a rare acne variant characterized by sudden onset of painful nodules on the face, chest, and back in the presence of systemic symptoms. Pharmacologic agents such as steroid hormones and isotretinoin are well-known triggers, and several cases have been described. We report a case of AF occurring a few days after lymecycline therapy initiation. Keywords: onset, systemic symptoms, steroids, trigger, isotretinoin, scars